Sherlock: Uma proposta de newsletter no LinkedIn contra a desinformação - Machado, Rodrigo Scapolatempore (2023)
"Sherlock: a proposal for a LinkedIn newsletter against disinformation" is an online communication product aimed at serving as a dynamic and collaborative forum to combat fake news within a specific social media platform. Its purpose is to bring together educators, journalists, scientists, fact-checking agencies, and academia to contribute as an additional protective measure for the right to accurate information, thereby defending democratic principles. With a social impact perspective and encouragement for professional journalism, the work delves into the theoretical foundation of the "newsletter" format and the term "disinformation," highlighting its harmful effects. It also contextualizes the power of social media and digital speed as conduits for spreading this issue while emphasizing that they are also the places from which it can be combated. With the commercial name "Sherlock, your magnifying glass against fake news", the product has been developed and adapted to work within the LinkedIn platform, whose profile is also detailed in the report. In line with the characteristics of a Professional Master's program, the practical aspect is presented as a real communication piece, with an applied perspective, featuring visual and graphic identity, a defined editorial line, launch schedule, and publication models to go live, functioning as a real business.